FILIAÇÃO: AS CRIANÇAS SEM A PATERNIDADE BIOLÓGICA DECLARADA NO REGISTRO E A PATERNIDADE SOCIOAFETIVA (REMUNOM, 2023)
This article seeks to discuss the relationship between children without biological paternity declared on record and socio-affective paternity, which is increasingly common in the Brazilian legal system. It is known that the forms of affiliation have evolved over time, with historical milestones for their evolution. Although biological filiation is a right of all children born in Brazil, both maternal and paternal, it is common to find children with records that do not contain such information, mostly with regard to paternity. Furthermore, even with biological affiliation on record, it is currently common to include socio-affective paternity in records. For the dissertation, the Federal Constitution, the Civil Code, the Child and Adolescent Statute, as well as contributions from renowned authors and jurisprudential understandings will be used as a basis.